PERFORMANCE AND PRODUCTIVITY MANAGEMENT IN THE FOOD INDUSTRY: A CASE STUDY APPLIED TO A SMALL-SCALE AGROINDUSTRY - Pereira, Pollyanna Cardoso; Junho, Diego Augusto Carneiro; Da Silva, João Pedro (Seven Editora, 2026)
Performance and productivity management in the food industry constitutes a strategic factor to ensure competitiveness, quality, and sustainability, especially in micro and small agro-industries. This chapter presents an integrated analysis between theoretical foundations and practical application, addressing tools such as Statistical Process Control (SPC), performance indicators, the seven quality tools, Knowledge Management, and Business Intelligence. The case study conducted in a small dairy plant located in Minas Gerais aimed to plan the expansion of a goat fine cheese production line, evaluating production capacity, mass balance, labor, and structural compliance. The results demonstrated the feasibility of the expansion through increased raw material supply, production rescheduling, targeted investments in infrastructure, and the hiring of an additional employee. The analysis showed that the structured use of indicators and management tools makes it possible to identify bottlenecks, reduce waste, and support strategic decisions based on data. It is concluded that the integration of theory and practice strengthens organizational competitiveness, even in contexts of limited resources, and highlights the role of data-driven management as a differentiating factor in the food industry scenario.